On Psychoanalysis - Seriously and with Humour (Antoni Cwoidzinsky's "Freud's Dream Theory") - Wzorek, Anna (Respectus Philologicus, 2006)
The article analyses "Freud's Dream Theory" that is one of the most popular and best Antoni Cwoidzinsky's between-war period work and that is considered one of the best works of scientific comedy. One of the goals of this work is to explain and illustrate the most important statements of psychoanalysis as clear as possible. Therefore, the article focuses upon the facts that the author writes seriously but with humour. On the one hand, Cwoidzinsky's comedy having two characters (He and She) reminds of scientific popular article on Freudism (the complexity of psychic, the mechanism of displacement and hidden symbolic meaning of dreams are discussed here ). On the other hand, this is a satire of Freudism. The article concludes that although the ideas are presented quite originally, the work contains quite a number of plot cliches that are characteristic of traditional trivial comedy.
Keywords: between-war period; scientific comedy; realistic drama; Antoni Cwoidzinsky; Freudism